System engineering of Singapore long-term care financing and delivery system - Fang, Kenneth Song Wei (2010)
The unique healthcare model of Singapore is formed by the combination of free market principles with careful government control. Singapore has gained extensive international recognition and praises and is ranked 6th in overall health system performance in the world. As Singapore continues to realize its National Health Plan, it has encountered challenges such as a rapid aging population and rising health care cost. The underdevelopment in Singapore long-term care delivery system and a lack of long-term care financing has led to a series of plans and initiatives undertaken by the government to rapidly develop this sector in order to meet the rising demands for long-term care services. Step-down care system was introduced to deliver a seamless care transition from acute hospitals to long-term care facilities to receive more appropriate treatments at a lower cost. Furthermore, financing policies were amended to increase in coverage and subsidies for long-term care services so to relieve the financial burden on the patient’s family.